2009
DOI: 10.1103/physreve.79.056403
|View full text |Cite
|
Sign up to set email alerts
|

Correlation effects on the temperature-relaxation rates in dense plasmas

Abstract: We present a model for the rate of temperature relaxation between electrons and ions in plasmas. The model includes self-consistently the effects of particle screening, electron degeneracy and correlations between electrons and ions. We successfully validate the model over a wide range of plasma coupling against molecular-dynamics simulations of classical plasma of like-charged electrons and ions. We present calculations of the relaxation rates in dense hydrogen and show that, while electron-ion correlation ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
99
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 27 publications
6
99
0
Order By: Relevance
“…Even for H, the demonstration of agreement between MD results and kinetic theory took some time [10][11][12][13], in part because the effect of using the QSPs changes the result slightly even in weak coupling [11]. For the classical like-charge proton-positron system, demonstration of agreement was somewhat more straightforward, motivating a clear connection between the classic LandauSpitzer equilibration rate [15] derived from the Fokker-Planck equation, and a generalized Lenard-Balescu [16] scheme in which both dynamical screening and 2-body static correlations (in the form of local field corrections) are included [8]. Furthermore, it was shown that for many regimes of interest to ICF, the complex dynamical screening of the 2-component (electron + proton) plasma could be replaced by the static response of the electrons alone, yielding identical results [8,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even for H, the demonstration of agreement between MD results and kinetic theory took some time [10][11][12][13], in part because the effect of using the QSPs changes the result slightly even in weak coupling [11]. For the classical like-charge proton-positron system, demonstration of agreement was somewhat more straightforward, motivating a clear connection between the classic LandauSpitzer equilibration rate [15] derived from the Fokker-Planck equation, and a generalized Lenard-Balescu [16] scheme in which both dynamical screening and 2-body static correlations (in the form of local field corrections) are included [8]. Furthermore, it was shown that for many regimes of interest to ICF, the complex dynamical screening of the 2-component (electron + proton) plasma could be replaced by the static response of the electrons alone, yielding identical results [8,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…All but a few of these studies [7,11,14] confined themselves to pure hydrogen (or the proton-positron system [8,9]). Even for H, the demonstration of agreement between MD results and kinetic theory took some time [10][11][12][13], in part because the effect of using the QSPs changes the result slightly even in weak coupling [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations